Synthesis of methylenebisamides using CC- or DCMT-activated DMSO - Wang, Qiang; Sun, Lili; Jiang, Yu; Li, Chunbao (Beilstein Journal of Organic Chemistry, 2008)
Bisamides are key fragments for the introduction of gem-diaminoalkyl residues into retroinverso pseudopeptide derivatives and in the synthesis of peptidomimetic compounds. The literature methods for these types of compounds have certain drawbacks. In particular, when amides react with electrophile-activated DMSO, the yields are rather low. We have found new electrophiles, 2,4,6-trichloro[1,3,5]triazine (CC) and 2,4-dichloro-6-methoxy[1,3,5]triazine (DCMT), which activate DMSO in the presence of amides to yield methylenebisamides in good to fair yields. The amides can be aromatic or aliphatic. The operation is simple and the reagents are inexpensive.
Keywords: amides; condensation; DMSO; methylenebisamides; 2,4,6-trichloro[1,3,5]triazine